2014
DOI: 10.1186/s12955-014-0114-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Alzheimer’s Disease on Caregiver Questionnaire: internal consistency, convergent validity, and test-retest reliability of a new measure for assessing caregiver burden

Abstract: BackgroundThere is a lack of validated instruments to measure the level of burden of Alzheimer’s disease (AD) on caregivers. The Impact of Alzheimer’s Disease on Caregiver Questionnaire (IADCQ) is a 12-item instrument with a seven-day recall period that measures AD caregiver’s burden across emotional, physical, social, financial, sleep, and time aspects. Primary objectives of this study were to evaluate psychometric properties of IADCQ administered on the Web and to determine most appropriate scoring algorithm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…Individuals suffering from dementia are affected by a progressive and significant global deterioration and, consequently, might require longer assistance in the advanced stage of the illness. 2 , 3 The person who takes care of a patient with dementia is known as a caregiver; in most cases, the caregiver is a family member. 4 …”
Section: Introductionmentioning
confidence: 99%
“…Individuals suffering from dementia are affected by a progressive and significant global deterioration and, consequently, might require longer assistance in the advanced stage of the illness. 2 , 3 The person who takes care of a patient with dementia is known as a caregiver; in most cases, the caregiver is a family member. 4 …”
Section: Introductionmentioning
confidence: 99%
“…One study was identified reporting on evaluation of the internal consistency, reliability and structural validity of this instrument [ 41 ]. Assessment of structural validity using confirmatory factor analysis confirmed unidimensionality of the scale.…”
Section: Resultsmentioning
confidence: 99%
“…There is also considerable variation in the settings and samples of included studies. Four studies [ 31 , 41 , 43 , 44 ] included only carers of people with Alzheimer’s disease, meaning that the results would not be generalizable to informal carers of people with other types of dementia. The studies on the QOL-AD (CQOL version) [ 43 , 44 ] and the SF-36 [ 31 ] used versions of the questionnaires in Portuguese and Argentinian respectively.…”
Section: Limitationsmentioning
confidence: 99%
“…Key demographic characteristics of the qualitative interview sample are shown in table 2. In addition, the sample had been caring an average of 54 months (range 5-180), 33 were co-resident with the person cared for, diagnoses of those cared for were Alzheimer's disease (18), vascular dementia (13), other dementia (9), type not known (2). Twelve of the people with dementia could not be left alone, 24 could be alone for up to half a day and seven for a whole day.…”
Section: Resultsmentioning
confidence: 99%
“…A systematic review [7] adhering to COSMIN methodology [15] identified ten measures used with dementia carer samples. Three of these measures were developed specifically for dementia carers, but two lacked evidence to recommend use [16,17] The third, Impact of Alzheimer Disease on Caregiver Questionnaire [18], is a unidimensional scale with fair to excellent psychometric qualities. However, further evaluation was advised including extending the sample to an older age group and to include carers of those with dementia other than Alzheimer's disease.…”
Section: Introductionmentioning
confidence: 99%